Islamic Business Ethics in Restaurant Marketing Strategy - Riza Lisvi Vahlevi, Dewi; Dhealita Suwoto, Arlisa (Institut Agama Islam YPBWI Surabaya, 2024)
Islamic business is a business activity based on Islamic principles whose every activity aims to always remember Allah in order to worship and produce benefits not only for themselves but also for the people around them. Marketing strategy is a set of programs used by entrepreneurs to promote a product either goods or services so that it can have a higher profit value compared to previous sales.The purpose of this study was to determine the marketing strategy in Lodho Ayam Kampung Yolla Restaurant Islamic business ethics from sales at the. in this study using observation, interview and documentation methods. For data analysis techniques used are data reduction, data presentation and conclusions. From the results of the research that has been done, it shows that the marketing strategy used is through radio and word of mouth. The most effective is the strategy used by word of mouth.The application of marketing strategies carried out by the Lodho Ayam Kampung Yolla Restaurant in terms of the principles of Islamic business ethics includes tawhid, which is always friendly with consumers, then balance, always being fair when serving without discriminating. The third is freedom. Where as a seller must give consumers the freedom to choose the product they want. Next is honesty, not exaggerating when promoting. The goods sold are beneficial to others and halal. Finally, giving wages according to the agreement with the employee at the beginning.